El comportamiento del ciudadano organizativo - Guerrero Bejarano, María Auxiliadora (2017)
The organizations are institutions made up of people who usually have a common goal, but although in general all comply with this principle, do not always achieve the same results, for some time academics have been trying to analyze the reason for this difference, and due to This has been studied for decades the different factors that could influence the performance of organizations. Among these factors is the behavior of the organizational citizen, the name with which the member of the organization is known which generally demonstrates higher levels of commitment to it, this theoretical analysis seeks to describe in a theoretical way the definition of this member who can influence positively In the results obtained by the company.